Implementation of the Government Performance Accountability System (SAKIP) at Makassar Port Authority - Darmawati Darmawati; Mujahid Mujahid; Abdul Samad (Journal of Management and Administration Provision, 2025)
This study examines the implementation of the Government Performance Accountability System (SAKIP) at the Makassar Port Authority, focusing on how it enhances institutional accountability and the challenges encountered during its execution. The research employs a qualitative design involving in-depth interviews, document analysis, and direct observation with key informants from various divisions of the Makassar Port Authority. Data were analyzed to identify patterns, supporting factors, and obstacles influencing the effectiveness of SAKIP implementation. The findings indicate that SAKIP has contributed to greater transparency, improved performance reporting, and more efficient budget utilization within the institution. Strong leadership commitment and coordination between divisions have enabled the system to operate effectively, resulting in several performance awards from the Ministry of Transportation and the Ministry of Finance. Nevertheless, challenges remain, including a shortage of human resources skilled in SAKIP, limited budget allocations, and weak integration of data management systems. These factors hinder optimal performance evaluation and timely reporting. The study concludes that successful implementation of SAKIP depends on continuous human resource development, the availability of adequate technological support, and active supervision by internal control units. The findings offer important implications for strengthening public sector accountability in Indonesia by integrating capacity building, digital governance, and performance-based evaluation. The study contributes to the growing body of literature on public accountability and provides a practical framework for enhancing governance quality across government agencies.